2018
DOI: 10.1097/brs.0000000000002502
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Accuracy of Thoracolumbar Minimally Invasive Pedicle Screw Placement With Augmented Reality Navigation Technology

Abstract: Study Design.Cadaveric laboratory study.Objective.To assess the feasibility and accuracy of minimally invasive thoracolumbar pedicle screw placement using augmented reality (AR) surgical navigation.Summary of Background Data.Minimally invasive spine (MIS) surgery has increasingly become the method of choice for a wide variety of spine pathologies. Navigation technology based on AR has been shown to be feasible, accurate, and safe in open procedures. AR technology may also be used for MIS surgery.Methods.The AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 21 publications
1
84
1
1
Order By: Relevance
“…Combined with MR, it can assist virtual positioning, give doctors the correct positioning point and direction when punctured, make the procedure more accurate and safer, is easy to operate, and obviously reduce the number of fluoroscopy and operation time. Elmi-terander et al [46] confirmed that combined with intraoperative 3D image, navigation technology is expected to replace intraoperative X-ray or fluoroscopy in the process of thoracolumbar pedicle puncture and has high accuracy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with MR, it can assist virtual positioning, give doctors the correct positioning point and direction when punctured, make the procedure more accurate and safer, is easy to operate, and obviously reduce the number of fluoroscopy and operation time. Elmi-terander et al [46] confirmed that combined with intraoperative 3D image, navigation technology is expected to replace intraoperative X-ray or fluoroscopy in the process of thoracolumbar pedicle puncture and has high accuracy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the surgical field recorded by 4 cameras with different angulations was shown on a high-definition monitor with the superimposition of 2D and 3D images of the vertebral segments together with the drilling trajectory. 52 The studies showed that ARSN resulted in a higher accuracy of thoracic pedicle screw placement compared to the FH technique without the need for intraoperative fluoroscopy or prior surgeon training. 51 Moreover, the system proved to be efficacious even when adopting a minimally invasive approach with the percutaneous placement of Jamshidi needles to determine screw entry point and orientation.…”
Section: Augmented Reality In Spine Surgerymentioning
confidence: 99%
“…Recent improvements in hardware that can function within traditional operative workflow and fit into the sterile environment, AR can also support intraoperative navigation for a wide set of orthopedic procedures, including fracture fixation and bone tumor resection . In a study by Wang et al, the investigators utilized a three‐dimensional reconstruction of patient CT data displayed on the HoloLens head‐mounted device for placement of a sacroiliac screw.…”
Section: Applications In Orthopedic Surgerymentioning
confidence: 99%
“…Left: Video see-through displays provide the user with a video feed of the surrounding real world combined with computer-generated graphics. Right: Augmented reality optical see-through devices project computer-generated graphics on a transparent lens, allowing the user to directly visualize the surrounding real-world surfaces with augmented overlayRecent improvements in hardware that can function within traditional operative workflow and fit into the sterile environment, AR can also support intraoperative navigation for a wide set of orthopedic procedures, including fracture fixation and bone tumor resection [46][47][48]. In a study by Wang et al, the investigators utilized a three-dimensional reconstruction of patient CT data displayed on the HoloLens headmounted device for placement of a sacroiliac screw.…”
mentioning
confidence: 99%